Analysis of chromosomal structural variations in patients with recurrent spontaneous abortion using optical genome mapping - Rao, Huihua; Zhang, Haoyi; Zou, Yongyi; Ma, Pengpeng; Huang, Tingting; Yuan, Huizhen; Zhou, Jihui; Lu, Wan; Li, Qiao; Huang, Shuhui; Liu, Yanqiu; Yang, Bicheng (Frontiers in Genetics, 2023)
Background and aims: Certain chromosomal structural variations (SVs) in biological parents can lead to recurrent spontaneous abortions (RSAs). Unequal crossing over during meiosis can result in the unbalanced rearrangement of gamete chromosomes such as duplication or deletion. Unfortunately, routine techniques such as karyotyping, fluorescence in situ hybridization (FISH), chromosomal microarray analysis (CMA), and copy number variation sequencing (CNV-seq) cannot detect all types of SVs. In this study, we show that optical genome mapping (OGM) quickly and accurately detects SVs for RSA patients with a high resolution and provides more information about the breakpoint regions at gene level. Methods: Seven couples who had suffered RSA with unbalanced chromosomal rearrangements of aborted embryos were recruited, and ultra-high molecular weight (UHMW) DNA was isolated from their peripheral blood. The consensus genome map was created by de novo assembly on the Bionano Solve data analysis software. SVs and breakpoints were identified via alignments of the reference genome GRCh38/hg38. The exact breakpoint sequences were verified using either Oxford Nanopore sequencing or Sanger sequencing. Results: Various SVs in the recruited couples were successfully detected by OGM. Also, additional complex chromosomal rearrangement (CCRs) and four cryptic balanced reciprocal translocations (BRTs) were revealed, further refining the underlying genetic causes of RSA. Two of the disrupted genes identified in this study, FOXK2 [46,XY,t(7;17)(q31.3;q25)] and PLXDC2 [46,XX,t(10;16)(p12.31;q23.1)], had been previously shown to be associated with male fertility and embryo transit. Conclusion: OGM accurately detects chromosomal SVs, especially cryptic BRTs and CCRs. It is a useful complement to routine human genetic diagnostics, such as karyotyping, and detects cryptic BRTs and CCRs more accurately than routine genetic diagnostics.